The School Support to the Implementation of Counseling Services during COVID-19 Pandemic at Public Vocational Schools in Semarang City - Awalya, Awalya; Nusantara, Boby Ardhian; Khiyarusoleh, Ujang; Lestari, Indah; Gumelar, Fikri Arif (Jurnal Bimbingan Konseling, 2022)
This study strived for exploring the institutional support to the implementation of guidance and counseling services. Online guidance and counseling services during COVID-19 pandemic requires practical mastery of information technology systems and gives big challenges for counselors’ roles and technological advancement mastery as well as professionalism. That is why guidance and counseling services need institutional support to get its maximum results. Here, this study used a survey design in form of cross-sectional and involved 333 participants, namely guidance and counseling teachers at Public Vocational Schools (SMK Negeri) in Semarang City. Those respondents were sampled using a simple random sampling technique, while their data were analyzed using descriptive statistics. Further, it is concluded that the support given by the schools to the implementation of counseling services during COVID-19 pandemic at SMK Negeri throughout Semarang City is considered fair and not yet maximum.